Challenges in Foot and Ankle Reconstructive Surgery A Case-based Approach - Visser, Harry J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Comprised exclusively of clinical cases, this concise, practical casebook provides clinicians and surgeons with current reconstructive techniques for complicated manifestations of foot and ankle injuries as a result of trauma, neuromuscular disease and deformity. Presenting unique cases in forefoot, midfoot, rearfoot, and ankle surgery, it is sensibly divided into six sections: forefoot maladies, the varus foot and ankle, the valgus foot and ankle, Charcot neuropathy, tendinopathies, and ankle joint revision. Each section demonstrates the surgical techniques chosen in each case, supported by generous, detailed surgical and radiographic slides and diagrams. A consistent chapter format, outlining the case presentation, diagnosis, management, and pearls and pitfalls, ensures its utility and accessibility. Pragmatic and reader-friendly, Challenges in Foot and Ankle Reconstruction Surgery: A Case-based Approach is an excellent resource for foot and ankle surgeons, podiatrists and all clinical staff treating these common yet challenging conditions.
Part I. Forefoot Maladies -- Revision of Lapidus, antibiotic spacer 2nd MTPJ -- Revision of Lapidus, interposition biofoam wedge, CC arthodiastatic via TN fusion -- Revision of Lapidus with interpositional fresh femoral head allograft and akin, gastroc recession -- Revision of trauma after Austin bunionectomy, locking plates x2 applied -- Revision of bunionectomy with 1st MT head resection, interpositional fresh femoral head allograft/bone marrow aspirate, locking bridge plate -- Removal of Laporta implant, allomatrix in canals, interposition 1st MTPJ -- Congenital brachymetapody -- Part II. Varus Foot and Ankle -- Cuboid reconstructed with fibula, reattachment -- STJ arthrodesis, arthrodesis of 5th MT shaft to 4th MT base -- Talectomy via transfibular approach, locking plate -- TA tendon tranfer to lateral cuneiform -- AVN of talus secondary to Charcot. Talectomy via transfibular approach, interposition of allograft in reamed tibial and calcaneal sites, application of internal bone stimulator -- Talar AVN. Transfibular approach, resection of tibia and calcaneus, back filling with bone chips. Rigid construct to allow for back filling of gap -- Intrinsic talar tilt in varus. Evans, PB tenodesis, lateral ankle stabilization, deltoid peel, tibialis posterior intratendinous lengthening -- Part III. Valgus Foot and Ankle -- Mueller-Weiss disease reconstruction -- Revision of flatfoot recon. Removal of subtalar screws, revision of STJ arthrodesis. Repeat gastroc recession, derotation osteotomy of TN malunion, removal non-union allograft medial cuneiform arthrodesis of 1st TMT -- Revision of failed triple arthrodesis. Re-alignment of ankle by resection of medial malleolus, femoral head allograft, lateral stabilization plate -- Severe fibular-calcaneal impingement secondary to valgus rearfoot position. Performed talectomy, tibiocalcaneal arthrodesis with IM nail, arthrodesis of 1st MTPJ and hammertoe repair -- Semi-rigid flatfoot in 15 yo M. Treated with sub-capital talar head wedge, Z-plasty tendo achilles lengthening, Koutsigiannis osteotomy -- PT tear. Baumann gastroc recession, double calcaneal osteotomy, Koutsigiannis calc osteotomy, PB to PL transmer inframalleolar, Evans, spring ligament repair, FDL transfer -- Subtalar arthrosis with valgus deformity. Repaired by revision of STJ via Achilles tendon split tendon approach to expose posterior facet. Joint backfilled with BMA and DBM and cancellous chips with 2 parallel fully threaded screws -- Part IV. Charcot Neuropathy -- Biplane transpedal wedge, gastroc recession, posterior calcaneal osteotomy -- Beaming screws to medial and lateral columns, locking plate medially -- Schon type II/III treated with triple arthrodesis with beams, medial column naviculectomy with grafting using beaming technique, protected with Ex-fix -- Bimalleolar fracture. ORIF 5 weeks post injury. Multiple tetrasystesmotic screw fixation, percutaneous screw fixation of medial malleolus -- Ankle fx with IM nail, no joint preparation -- Part V. Tendinopathies -- Hunter rod peroneal reconstruction -- Dwyer osteotomy, excision of peroneal tendons, insertion of peroneal tendon allograft -- Lateral calcaneal osteotomy, FDL transfer to PB stump -- D.P -- Infection secondary to graft jacket. Treated by open Z-plasty and FHL tendon transfer -- Revision of Achilles tendon repair. Treated by resection of Achilles and transfer FHL an FDL -- Repair of insertion of TA tendon -- Part VI. Ankle Joint Revisions -- Tibial calcaneal arthrodesis with IM nail -- Removal of ankle implant, ankle arthrodesis with interpositional bone graft -- Revision of INBONE TAR. 50% talar surface replaced with iliac crest bone graft strut.
Keywords: Orthopedics; Sports medicine; Orthopaedics; Sports Medicine; Foot -- surgery; Ankle -- surgery; Foot Injuries -- surgery; Ankle Injuries -- surgery; Plastic Surgery Procedures -- methods; Case Reports